Sintesis Nanopartikel Perak Menggunakan Ekstrak Daun Bidara Ziziphus Spina-Christi Dan Uji Aktivitas Antibakteri Terhadap Bakteri Staphylococcus Aureus - Cut Dian Mala Luthfia; Dikki Miswanda; Haris Munandar Nasution; Minda Sari Lubis (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Nanotechnology is currently growing rapidly due to its broad application in science and technology. Nanotechnology itself is a science based on nanoparticles, so a more environmentally friendly method is being developed, namely the